BaTiO3-filled epoxy resin composites: Numerical modelling of dielectric constants - Ramajo, Leandro Alfredo (2006)
The influence of BaTiO3 content on the composite dielectric properties was investigated by finite element method (FEM). This method is attractive because of its technological applications such as those in electromagnetic shields, since it allows to determine the dielectric constant of heterogeneous mediums and show or display the electric field into the material in order to understand the interfacial behaviours. The dielectric response of an anisotropic and periodic heterostructure, was evaluated and quantified by means of a quasistatic approximation using Laplace`s equation which was solved by 3D FEM. The numerical calculations were confronted with experimental data. Measurements of the effective permittivity were carried out in samples prepared by dipping technique.